THE UTILIZATION OF SOCIAL MEDIA IN EFL HIGHER EDUCATION CLASSROOM CONTEXT - Bunga Citra Dewi; Sherly Agustiana; Riska Riska; Hanif Nurcholis Adiantika (University of Kuningan, 2023)
This study aims to explore how EFL students use social media to learn English. This exploratory study investigated the use of social media platforms for English language acquisition. The data were obtained through a survey and a semi-structured interview. Sixty-seven students responded to the questionnaire and ten students were purposively selected from the participants who responded to the questionnaire for an interview. Quantitative data from the questionnaire were analyzed using basic statistical methods, whilst interview data were evaluated using phenomenological case analysis and thematic coding. Students utilize numerous social media platforms, including Instagram and Facebook, according to the research. The findings indicate that students spent more time utilizing social media for non-academic objectives than for English study. However, they demonstrated a favorable attitude toward the use of social media in English language acquisition. Students believe social media has a significant influence in enhancing their English language skills. In addition, it encourages students to use social media to improve their English language skills.Keywords: ICT, social media, EFL classroom